2010
DOI: 10.1371/journal.pone.0010621
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Epidemiology of Attention Deficit Hyperactivity Disorder (ADHD Index) in Adults

Abstract: ContextIn contrast to the large number of studies in children, there is little information on the contribution of genetic factors to Attention Deficit Hyperactivity Disorder (ADHD) in adults.ObjectiveTo estimate the heritability of ADHD in adults as assessed by the ADHD index scored from the CAARS (Conners' Adult ADHD Rating Scales).DesignPhenotype data from over 12,000 adults (twins, siblings and parents) registered with the Netherlands Twin Register were analyzed using genetic structural equation modeling.Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
110
3
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 122 publications
(133 citation statements)
references
References 44 publications
16
110
3
1
Order By: Relevance
“…First, reports of childhood/adolescent behavior were retrospective and might have been subject to recall bias; this could account for the fact that our heritability estimates of ADHD factors were lower than previous studies (Faraone et al, 2005), most of which reported estimates greater than or equal to 0.6. However, our estimate is in agreement with others from retrospective reports (Haberstick et al, 2008) and with an estimate of the heritability of adult ADHD (Boomsma et al, 2010). In addition, assessments from other reporters (parents, teachers) could reduce error in the measure of adolescent behavior; such reports are unavailable for this sample.…”
Section: Limitationssupporting
confidence: 91%
“…First, reports of childhood/adolescent behavior were retrospective and might have been subject to recall bias; this could account for the fact that our heritability estimates of ADHD factors were lower than previous studies (Faraone et al, 2005), most of which reported estimates greater than or equal to 0.6. However, our estimate is in agreement with others from retrospective reports (Haberstick et al, 2008) and with an estimate of the heritability of adult ADHD (Boomsma et al, 2010). In addition, assessments from other reporters (parents, teachers) could reduce error in the measure of adolescent behavior; such reports are unavailable for this sample.…”
Section: Limitationssupporting
confidence: 91%
“…For instance, an increasing number of stressful life events increase the risk for anxiety disorders (Blazer et al 1987), which may deflate the phenotypical correlation and increase the non-shared environmental factors. The heritability of ADHD has indeed been found to be substantially lower in adulthood than in childhood in other studies (Boomsma et al 2010), indicating that unique environmental influences act in concert with the genotype. Of note, the proportion of unique environmental factors operating across ALTs and ADHD traits and across ALTs and anxiety traits was higher in adults than in children.…”
Section: Discussionmentioning
confidence: 77%
“…However studies of twin studies of self-rated ADHD symptoms among adult population report lower estimates of heritability of around 30-40%. 42,43 There were no gender differences observed in the heritability estimates. Adoption studies show that ADHD is passed on only to biological relatives, which strongly suggests genetic factors playing a significant role causing high familial risk of the disease.…”
Section: Pathophysiology Clinical Features and Treatment Optionsmentioning
confidence: 84%